Species of Coenosia Meigen (Diptera, Muscidae) described by Fritz van Emden from the British Museum Ruwenzori Expedition of 1934–1935 - Couri, Márcia; Pont, Adrian (Zootaxa, 2016)
All the species of Coenosia Meigen (Diptera, Muscidae) described by Fritz van Emden from the British Museum (Natural History) Ruwenzori Expedition of 1934–1935 (Emden 1940), supplemented by species from the Entomological Expedition to Abyssinia of 1926–1927 (Emden 1941), were studied, a total of 51 species. All types are deposited in the Natural History Museum, London, UK. For each species, a diagnosis is given and photographs of the 10 holotypes and of their labels are presented. Dissections and illustrations of the male terminalia were made when paratypes or identified specimens were available; all terminalia are described for the first time. One new synonym is proposed: C. kilembana (Emden, 1940) as a junior synonym of C. rebmanni Speiser, 1924; and three subspecies had their status revised and were elevated to species rank: C. brunneigena Emden, 1940, previously a subspecies of C. heterocnemis Emden, 1940; and C. albisquama (Emden, 1940) and C. argentescens (Emden, 1940), both previously subspecies of C. niveifrons (Stein, 1913).